Group and longitudinal intra-individual networks of eating disorder symptoms in adolescents and young adults at-risk for an eating disorder - Levinson, Cheri A.; Vanzhula, Irina A.; Smith, Tosha Woods; Stice, Eric (Behaviour research and therapy, 2020)
Several studies have identified risk factors that predict future onset of eating disorders (ED) in adolescence, however, it is currently unknown how specific ED symptom dynamics operate both across time and within individuals. Advances in network methodologies allow for the study of how dynamic symptoms interrelate and predict each other within-persons and across time. In the current study, we used longitudinal group-level (N = 1272) (addressing symptom interrelations across people and across time; between-subjects, contemporaneous, and temporal networks) and intra-individual (symptom interrelations within each person and across time; contemporaneous and temporal networks) network analyses (subset n = 50) in prospective 48-month interview data in at-risk adolescents and young adults. We computed between-subject networks (how symptoms are associated on average, for group sample only), contemporaneous networks (how symptoms are associated at one time point, accounting for previous time points), and temporal networks (examining how symptoms predict each other across time). We replicated prior network results which suggest that overvaluation of weight and shape are central in at-risk adolescents and young adults. We found that individual networks (n = 1 networks) were highly variable across individuals. Overall, our results show how both group-level and longitudinal intra-individual network analysis can inform our understanding of how EDs develop in adolescence and point to the importance of conceptualizing development on an individual level of analysis. •It is unknown how specific eating disorder (ED) symptom dynamics operate across time and within individuals.•The current study constructed group (N = 1272) and individual (N = 50) longitudinal networks of ED symptoms across 48-months.•We found that overvaluation of weight and shape are central symptoms in at-risk adolescents.•We also found that networks were highly variable across individuals.